1961
DOI: 10.1016/s0006-3495(61)86890-2
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Weight and Aggregation of DNA

Abstract: The effects of enzymatic attack and of shear during the isolation and deproteinization of DNA have been investigated. Different methods of disaggregating DNA have been studied, and conditions under which reaggregation can occur are discussed. It was found that shaking with chloroform-octanol does not degrade DNA from the seven sources studied; that light scattering yields valid weight-average molecular weights for these samples; and that, when disaggregated, the molecular weights of these samples are in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1961
1961
1976
1976

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…It is of course possible that the subunits separating at the completion of denaturation are paired double helices (18), but since the separation appears to be related to the dissociation of base pairs (see also (1)) we presently prefer the postulate of strand separation.…”
Section: Discussionmentioning
confidence: 99%
“…It is of course possible that the subunits separating at the completion of denaturation are paired double helices (18), but since the separation appears to be related to the dissociation of base pairs (see also (1)) we presently prefer the postulate of strand separation.…”
Section: Discussionmentioning
confidence: 99%
“…The mixtures were then allowed to cool slowly to room temperature. The preparation of calf-thymus DNA has been described (5). Activated DNA was prepared according to the procedure of Aposhian and Kornberg (6).…”
Section: Methodsmentioning
confidence: 99%
“…When the light scattering measurements are carried out immediately after denaturation, no aggregation is observed in the concentration range 0.04 to 0.15 mg/ml (19); consequently, the apparent constancy of molecular weight cannot very readily be attributed to aggregation. In addition, a study of the de crease in molecular weight as a function of the number of bonds hydrolyzed by DNase II indicated that there was no change in the number of strands per molecule upon denaturation [Cavalieri & Rosenberg (69)].…”
Section: Denaturationmentioning
confidence: 97%
“…A wide range of particle weights by light scattering has been reported, but the values have centered around 6 to 8 million, with some as high as 16 million [Shooter (13) ; Hermans (14) ; Fleischman (15)]. The problem of protein and metal ion contamination has been recognized [Butler,Robins & Shooter (17) ; Kirby (18)1 and its role in molecular-weight determination has been emphasized recently by Cavalieri, Deutsch & Rosenberg (19). In a systematic study of molecular weights of DNA s a mples from seven sources, these authors have shown that the weights, after exhaustive disaggregation treatment, lie in the range 0.6 to 2 million.…”
Section: Molecular Weight and Aggregationmentioning
confidence: 99%
See 1 more Smart Citation